ANALYSIS ON THE USE OF ENGLISH IN ECONOMIC MATHEMATICS TEACHING AND LEARNING (EXPERIMENTAL STUDY IN UNIVERSITAS ADVENT INDONESIA) - Saija, Louise M; Sihotang, Ronny B (LPPM Universitas Advent Indonesia, 2018)
English language is an International language. This makes the use of English in teaching-learning process in countries, where English is generally not a local medium of communication, become important. Mathematics is also very important for every student, but several previous research showed that students had difficulty in learning this subject. The purpose of this experimental study is to see the effectiveness of the use of English in teaching-learning process of economic mathematics towards economic undergraduate students. The result shows us that students who learn mathematics with English-medium system have better achievement than students who learn mathematics with local language. Another finding was students learn mathematics more enthusiastic when the teaching-learning process is made with the language they chose.Keyword: English language, economic mathematics, teaching learning.